Striking the Right Chord: Insights for Taxonomy Harmonization from a Comparative Analysis of Six Sustainable Finance Taxonomies - Welch, Caelan (Université d'Ottawa / University of Ottawa, 2025)
Achieving the objectives of the Sustainable Development Goals and the Paris Agreement requires unprecedented levels of investment. However, mobilizing sufficient public and private sector capital faces persistent barriers, including the lack of shared definitions for what constitutes a 'sustainable' investment. Sustainable finance taxonomies - classification systems that identify and define activities or assets considered sustainable for investment purposes - have emerged as critical tools for establishing detailed sustainability definitions, with a growing number of national and regional governments developing them to support their sustainable finance markets. However, limited coordination in taxonomy development has raised concerns about market fragmentation due to inconsistent approaches. While this has prompted calls for taxonomy harmonization to promote consistent sustainability definitions globally, the literature also recognizes a need to ensure taxonomies reflect local context and priorities. This introduces complexity for harmonization efforts, which must balance achieving globally consistent definitions while accommodating appropriate local differences. In this context, this thesis utilizes a comparative case study approach to examine six sustainable finance taxonomies developed by Bangladesh, China, the Climate Bonds Initiative, the European Union, and Mongolia. Through systematic analysis guided by a structured case framework developed for this research, the study builds understanding of existing approaches to taxonomy design and considers the implications of these findings in relation to reconciling the harmonization imperative of ensuring globally consistent sustainability definitions with the realities of how the taxonomy landscape is evolving across developed and developing economies. The analysis reveals that while these taxonomies share many overarching features of design, there are notable variations in their approaches. This includes different classification structures that diminish comparability without serving a clear purpose, inconsistent operationalization of shared underlying concepts, and sustainability definitions that vary considerably due, in large part, to local considerations. Based on these findings, the thesis proposes three harmonization-focused action areas. First, developing a global structural framework could establish a common foundation for organizing and presenting sustainability definitions within taxonomies. Second, strengthening alignment of key underlying concepts could improve definitional consistency across taxonomies. However, the analysis underscores that harmonization should go beyond eliminating differences to accommodate appropriate local variation. Therefore, a third action area via international cooperation is proposed: mutual recognition of taxonomies' sustainability definitions. This balanced approach aims to improve overall comparability of taxonomies' definitions while ensuring that appropriate differences reflecting local context do not unnecessarily hinder cross-border flows of sustainability-aligned investment.
Keywords: Sustainable Finance Taxonomies; Taxonomy Harmonization; Sustainable Finance; Green Finance; Taxonomy Interoperability; Definitions